The genomes of the yaws bacterium, Treponema pallidum subsp. pertenue, of nonhuman primate and human origin are not genomically distinct. - Klára Janečková; Christian Roos; Pavla Fedrová; Nikola Tom; Darina Čejková; Simone Lueert; Julius D Keyyu; Idrissa S Chuma; Sascha Knauf; David Šmajs (Public Library of Science (PLoS), 2023)
Background Treponema pallidum subsp. pertenue (TPE) is the causative agent of human yaws. Yaws is currently reported in 13 endemic countries in Africa, southern Asia, and the Pacific region. During the mid-20th century, a first yaws eradication effort resulted in a global 95% drop in yaws prevalence. The lack of continued surveillance has led to the resurgence of yaws. The disease was believed to have no animal reservoirs, which supported the development of a currently ongoing second yaws eradication campaign. Concomitantly, genetic evidence started to show that TPE strains naturally infect nonhuman primates (NHPs) in sub-Saharan Africa. In our current study we tested hypothesis that NHP- and human-infecting TPE strains differ in the previously unknown parts of the genomes. Methodology/principal findings In this study, we determined complete (finished) genomes of ten TPE isolates that originated from NHPs and compared them to TPE whole-genome sequences from human yaws patients. We performed an in-depth analysis of TPE genomes to determine if any consistent genomic differences are present between TPE genomes of human and NHP origin. We were able to resolve previously undetermined TPE chromosomal regions (sequencing gaps) that prevented us from making a conclusion regarding the sequence identity of TPE genomes from NHPs and humans. The comparison among finished genome sequences revealed no consistent differences between human and NHP TPE genomes. Conclusion/significance Our data show that NHPs are infected with strains that are not only similar to the strains infecting humans but are genomically indistinguishable from them. Although interspecies transmission in NHPs is a rare event and evidence for current spillover events is missing, the existence of the yaws bacterium in NHPs is demonstrated. While the low risk of spillover supports the current yaws treatment campaign, it is of importance to continue yaws surveillance in areas where NHPs are naturally infected with TPE even if yaws is successfully eliminated in humans.